EFEKTIVITAS RASIO PINGGANG-TINGGI DAN TEKANAN DARAH PASCAPAPARAN STRESSOR AKUT COLD PRESSOR TES (CPT)TERHADAP RISIKO HIPERTENSI PADA MAHASISWA - Nurul Kartika Sari; Yehud Maryen; I Made Raka (Nursing Arts, 2020)
Data figures pain in City of Province of West Papua shows that hypertension is included in th 10 diseases most in the health center, which occupies the order of the 2nd after the disease malaria. Hypertension can be prevented and dealt with effectively order to decrease the risk of stroke and attack the heart through measurement anthropometrics and administration of cold exposures such as cold pressor tests (CPT). The purpose of this study was to determine the difference in the effect of waist-height rasio and blood pressure after exposure to acute stressor CPT on the risk of hypertension. This study uses a quasy-experimental research design with a two-group comparison post-test only design approach Mechanical taking sampling by way of simple random sampling. Variables that are used are age, type of sex, history of smoking history of alcohol, history of genetics and the risk of hypertension. The 64 samples in the group intervention and group control, respondents most aged <20 years either in group intervention or group comparison which amounted to 18 respondent (56.3%) , various sex women as much as 24 respondents (75%), did not have a history of smoking as much as 28 respondents (87.5%), did not have a history of al k ohol that as many as 30 respondents (93.8%) and 29 respondents (90.6%), have a history of genetic hypertension as much as 17 respondents (53.1%). Inaddition it also obtained the pressure of blood post- CPT worth normal numbering 29 people (90.6%) and the ratio of waist-high value- normal as much as 21 (65.6%). The results of the analysis of the statistics obtained that does not exist differences are significant between the TD after the CPT test with the risk of hypertension (p value = 0.238; α = 0.05). While the results of test statistical difference in the effect of the ratio of waist- high against the risk of hypertension indicates that there is a difference that is significant ratio of waist-high against the risk of hypertension ( p-value = 0, 000 ; α = 0.05). It was concluded that there were not significant between blood pressure after exposure to acute CPT stressor and waist-height ratio to the risk of hypertension. Keywords: Risk of Hypertension; Cold Pressor test; ratio of waist-high